The Effect of Tax Supervision on Taxpayer Compliance in Submitting Annual Tax Returns at DGT Bali Regional Offices - Ashari Nursetyo Nugroho; Rahmat Hidayat; Akadun (Journal Research of Social Science, Economics, and Management, 2025)
Despite high tax revenue realization at Indonesia’s DGT Bali Regional Office, formal compliance in Annual Tax Return (SPT) submissions remains critically low (41.18%–44.93%), signaling a gap between enforcement and taxpayer adherence. This study investigates how tax supervision influences compliance, addressing regional disparities overlooked in prior literature.The research aims to analyze the effect of tax supervision on taxpayer compliance in SPT submissions, assessing perceptual and operational dimensions of supervision. A quantitative survey of 214 taxpayers (cluster random sampling) used Likert-scale questionnaires, analyzed via descriptive statistics and simple linear regression (SPSS v27). Tax supervision significantly improves compliance (46.8% contribution), with supervision perceived as effective overall (3.83/5) but weaker in measurement (3.34/5). Compliance scored highly (4.42/5), driven by formal compliance. The study underscores the need for enhanced measurement tools in supervision and explores uncharted factors (e.g., digitalization, socio-cultural influences) affecting compliance. It provides actionable insights for regional tax authorities to refine policies, bridging the gap between revenue targets and taxpayer engagement.